4 - t = 3(t - 1) -5
slayzombiestn9pelkt3:
solve this equation***
Answers
Answered by
7
4-t=3t-3-5
4-t=3t-2
3t+t=4+2
4t=6
t=6/4=3/2
4-t=3t-2
3t+t=4+2
4t=6
t=6/4=3/2
Answered by
9
Hey !!
Here is ur answer !!❤❤
____________________________________________________
![4 - t = 3(t - 1) - 5 \\ 4 - t= 3t - 3 - 5 \\ 4 + 8 = 3t + t \\ 12 = 4t \\ t = 3 4 - t = 3(t - 1) - 5 \\ 4 - t= 3t - 3 - 5 \\ 4 + 8 = 3t + t \\ 12 = 4t \\ t = 3](https://tex.z-dn.net/?f=4+-+t+%3D+3%28t+-+1%29+-+5+%5C%5C+4+-+t%3D+3t+-+3+-+5+%5C%5C+4+%2B+8+%3D+3t+%2B+t+%5C%5C+12+%3D+4t+%5C%5C+t+%3D+3)
____________________________________________________
Hope this will help you
Please mark as brilliant !!❤❤
Here is ur answer !!❤❤
____________________________________________________
____________________________________________________
Hope this will help you
Please mark as brilliant !!❤❤
Similar questions
Chemistry,
8 months ago
English,
8 months ago
Math,
8 months ago
Math,
1 year ago
Environmental Sciences,
1 year ago